Email for clinical communication between healthcare professionals. - Goyder, C; Atherton, H; Car, M; Heneghan, C; Car, J (2015)
BACKGROUND: Email is one of the most widely used methods of communication, but its use in healthcare is still uncommon. Where email communication has been utilised in health care, its purposes have included clinical communication between healthcare professionals, but the effects of using email in this way are not well known. We updated a 2012 review of the use of email for two-way clinical communication between healthcare professionals. OBJECTIVES: To assess the effects of email for clinical communication between healthcare professionals on healthcare professional outcomes, patient outcomes, health service performance, and service efficiency and acceptability, when compared to other forms of communicating clinical information. SEARCH METHODS: We searched: the Cochrane Consumers and Communication Review Group Specialised Register, Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library, Issue 9 2013), MEDLINE (OvidSP) (1946 to August 2013), EMBASE (OvidSP) (1974 to August 2013), PsycINFO (1967 to August 2013), CINAHL (EbscoHOST) (1982 to August 2013), and ERIC (CSA) (1965 to January 2010). We searched grey literature: theses/dissertation repositories, trials registers and Google Scholar (searched November 2013). We used additional search methods: examining reference lists and contacting authors. SELECTION CRITERIA: Randomised controlled trials, quasi-randomised trials, controlled before and after studies, and interrupted time series studies examining interventions in which healthcare professionals used email for communicating clinical information in the form of: 1) unsecured email, 2) secure email, or 3) web messaging. All healthcare professionals, patients and caregivers in all settings were considered. DATA COLLECTION AND ANALYSIS: Two authors independently assessed studies for inclusion, assessed the included studies' risk of bias, and extracted data. We contacted study authors for additional information and have reported all measures as per the study report. MAIN RESULTS: The previous version of this review included one randomised controlled trial involving 327 patients and 159 healthcare providers at baseline. It compared an email to physicians containing patient-specific osteoporosis risk information and guidelines for evaluation and treatment versus usual care (no email). This study was at high risk of bias for the allocation concealment and blinding domains. The email reminder changed health professional actions significantly, with professionals more likely to provide guideline-recommended osteoporosis treatment (bone density measurement or osteoporosis medication, or both) when compared with usual care. The evidence for its impact on patient behaviours or actions was inconclusive. One measure found that the electronic medical reminder message impacted patient behaviour positively (patients had a higher calcium intake), and two found no difference between the two groups. The study did not assess health service outcomes or harms.No new studies were identified for this update. AUTHORS' CONCLUSIONS: Only one study was identified for inclusion, providing insufficient evidence for guiding clinical practice in regard to the use of email for clinical communication between healthcare professionals. Future research should aim to utilise high-quality study designs that use the most recent developments in information technology, with consideration of the complexity of email as an intervention.